BECOMING A UNIVERSITY STUDENT IN MIDAGE: GENDER ISSUES, NECESSARY REFLECTIONS - Vieira, Zoraide Santos; Santos, Cristina Silva dos; Oliveira, Maria Cristina dos Santos (Revista de Estudos em Educação e Diversidade - REED, 2022)
Debating the presence of middle-aged women at the university has proved to be of great importance for understanding contemporary society and for building public policies in the field of education The study aims to analyze the voices of women aged between 40 and 60 years and their challenges and confrontations in the process of insertion in higher education in the pedagogy course at UESB - Campus Itapetinga. The methodology used was a qualitative, descriptive approach, 12 women volunteers, aged between 40 and 60 years were part of the sample. Data were collected through a virtual form sent to the women’s email. The results were analyzed in order to broaden the understanding of the reality studied and demonstrated the naturalization of aspects of subordination of women in relation to men, in the power relations present in the traditional patriarchal family model. Public policies educational strategies capable of re-signifying the roles of women in the contemporary world.